Socioeconomic disparities in the associations of age at last live birth with stroke and its subtypes among Chinese parous postmenopausal women: A prospective cohort study - Shiyi Shan; Weidi Sun; Jing Wu; Leying Hou; Zeyu Luo; Jiali Zhou; Jiayao Ying; Peige Song (Experimental Gerontology)
Background: As a pivotal reproductive factor, age at last live birth (ALLB) plays a critical role in a woman's health trajectory, including the risk of cardiovascular diseases. Methods: In this prospective cohort study from the China Kadoorie Biobank (CKB), 148,456 parous postmenopausal women were included. ALLB was further classified equally into tertiles (<26 years, 26–29 years, and ≥30 years). Total stroke and its three subtypes (ischemic stroke [IS], intracerebral hemorrhage [ICH], and subarachnoid hemorrhage [SAH]) were identified as outcomes. Cox proportional hazard regression was performed to estimate hazard ratios (HRs) and 95 % confidence intervals (CIs) for the associations of ALLB with incident stroke and its subtypes. Latent class analysis (LCA) was employed to explore underlying socioeconomic status (SES) classes within women in urban and rural areas, and SES-stratified analysis was conducted. Population attributable fraction (PAF) was estimated to assess the impact of later ALLB on stroke at the population level. Results: Compared with women with ALLB of <26 years, women with later ALLB (26–29 years and ≥ 30 years) faced a higher risk of stroke, with the highest fully adjusted HRs (aHRs) observed in women whose ALLB was ≥30 years (total stroke: 3.88, 95 % CI 3.71–4.07; IS: 5.33, 95 % CI 5.05–5.63; ICH: 3.79, 95 % CI 3.36–4.29; SAH: 4.93, 95 % CI 3.41–7.12). The strongest associations were found among rural-low-SES participants with total stroke and IS, with aHRs of 5.61 (95 % CI 5.12–6.16) and 7.28 (95 % CI 6.51–8.14) for an ALLB of ≥30 years. The highest PAF of total stroke with ALLB ≥26 years was observed in rural-middle-SES individuals, with value of 59.15 % (95 % CI 56.80–61.48). Conclusion: Later ALLB was associated with an increased risk of stroke among Chinese parous postmenopausal women, notably in lower socioeconomic rural populations.